A mixed separation-immobilization method for soluble salts removal and stabilization of heavy metals in municipal solid waste incineration fly ash. (15th June 2019) - Atanes, Evangelina; Cuesta-García, Blanca; Nieto-Márquez, Antonio; Fernández-Martínez, Francisco
Abstract: This work presents the results of a treatment process of municipal solid waste incineration (MSWI) fly ash using a solution of sodium carbonate as a stabilizing agent. The effectiveness of the treatment was evaluated by means of leaching test for waste characterization according to European Standard, with special focus on soluble chlorides and heavy metals (Zn, Cd, Pb and Cu). Chemical, XRD and DTA/DTG analysis were used to gain insight into the chemical changes induced in the fly ash by the treatment. In the fresh fly ash, the total dissolved solids and chloride concentration exceed the acceptance limits for hazardous waste whereas fresh fly ash was classified as hazardous waste concerning Pb. The carbonated fly ash was considered as non-hazardous waste according to all studied parameters. XRD and DTA/DTG analysis of treated fly ash showed that chlorine compounds have been transferred into the liquid phase during the stabilization process. The chloride removal from the ash was complete and fast irrespective of the sodium carbonate concentration and solid/liquid ratio in the stabilization process within the range studied. The treated fly ash was mainly composed by calcite and portlandite and the chemical analysis after the leaching test demonstrated that more than 98% of heavy metals remained in the treated fly ash. Therefore, the stabilization procedure of MSWI fly ash with a solution of carbonate ions achieved the separation of soluble salts and the leaching stabilization of heavy metals simultaneously in one step. Highlights: A sodium carbonate treatment stabilized municipal solid waste incineration fly ash. The treatment decreased the environmental hazard of fly ash to non-hazardous waste. The method provided a fast and complete separation of soluble chloride. Heavy metals remained stabilized and non-leachable in the treated fly ash.